Dough mixing characteristics measured by Mixsmart software as possible predictors of bread making quality in three production regions of South Africa. (July 2016) - Labuschagne, M.T.; Lindeque, R.C.; van Biljon, A.
Abstract: South Africa has three wheat production regions, the winter rainfall region where spring wheat is planted; the summer rainfall where winter and intermediate wheat is cultivated; and the irrigation region where spring wheat is grown. The aim of this study was to determine dough mixing characteristics as measured by Mixsmart ® software in these three regions over seasons and locations, and to relate this to important quality characteristics. In the winter rainfall area Mixsmart characteristics were very poor predictors of baking quality, especially of loaf volume, flour protein content and wet gluten content. The best predictors of loaf volume in this region were flour protein content and wet gluten content, which were highly interrelated. In the irrigation area, midline peak value and midline right value were very good predictors of flour protein content, gluten content and loaf volume. Midline peak value was highly correlated with protein content in both the irrigation and summer rainfall areas and was a better predictor than peak time of baking quality. The ideal would be to select several parameters from the mixograph and use them in a multivariate statistical analysis to obtain a more accurate prediction of loaf volume in the irrigation and summer rainfall areas. Highlights: This study used Mixsmart characteristics to predict baking quality. In the winter dryland area Mixsmart was a poor predictor of quality. In the summer rainfall and irrigation areas Mixsmart was a good predictor of quality. Mixograph peak value was better than peak time to predict quality.